CAUSES AND DIAGNOSIS OF INFERIENCE IN HIGH PRODUCTIVE COWS - Alimov Bakhrom Sayfiyevich; Yunusov Khudoynazar Beknazarovich; Eshburiyev Bakhtiyor Mamatkulovich (Ecominds Press, 2025)
This article presents literature data on the causes and methods of diagnosis of infertility in cows with high milk production. Also, the results of obstetric and gynecological medical examinations in highly productive cows are given.
Keywords: Cow, high-yielding, infertile, hormone, diagnostic, hypofunction, ovarian, pituitary, hypothalamus, minerals and vitamins.